Malay responses to online invitation from a gender perspective / Nur Fatihah Mohd Zamani - Mohd Zamani, Nur Fatihah (2014)
From the perspective of sociolinguistics, little is known on how Malay online responses are mediated. With this in mind, the two main objectives of this study are (a) to examine the structural elements of online responses across gender and (b) to examine the linguistic elements of online responses across gender. A contextual analysis using qualitative and quantitative approaches was used for the study of 103 Facebook online wedding invitations, involving 1475 male and 3233 female Malay responses (henceforth Tokens). In the construction of the analysis, the following frameworks were adopted: Al-Khatib’s Classification of Acceptance (2006) and Beebe et al’s Classification of Refusal (1990). In addition, Swales’ moves and steps structure and Searle’s five (5) points of speech acts were also used in analysing the data. The findings of the study reveal that for both males and females, the obligatory and optional moves can be seen for token of affirmative and tentative, while only obligatory moves can be noted for both genders in the token of decline. Nonetheless, the obligatory and optional moves for both genders differ for each token of affirmative, tentative and decline. As for linguistic elements, two (2) speech acts, namely expressive and commissive, have been found used by males while three (3), namely expressive, directive and commissive, have been applied by female informants in their responses. The significance of this study serves twofold: (a) provide a better understanding on how males and females handle online invitations, and (b) giving insights as to how language variation in terms of speech acts is applied upon responding to online invitations across gender within a sociolinguistic framework.